2015
DOI: 10.1130/g36961.1
|View full text |Cite
|
Sign up to set email alerts
|

Transient changes of landslide rates after earthquakes

Abstract: Earthquakes impart an impressive force on epicentral landscapes, with immediate catastrophic hillslope response. However, their legacy on geomorphic process rates remains poorly constrained. We have determined the evolution of landslide rates in the epicentral areas of four intermediate to large earthquakes (M w , 6.6-7.6). In each area, landsliding correlates with the cumulative precipitation during a given interval. Normalizing for this meteorological forcing, landslide rates have been found to peak after an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
257
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 205 publications
(284 citation statements)
references
References 26 publications
20
257
2
Order By: Relevance
“…The decreasing temporal effect of earlier landslides on susceptibility is to some extent comparable with the legacy effect of earthquakes on the occurrence of earthquake-induced landslides (Lin et al 2007;Marc et al 2015;Parker et al 2015). For instance, Marc et al (2015) demonstrated that landslide rates were significantly elevated within 0.7-4.5 years after four earthquakes with magnitude higher than 6 Richter.…”
Section: Are Follow-up Landslides Different?mentioning
confidence: 69%
“…The decreasing temporal effect of earlier landslides on susceptibility is to some extent comparable with the legacy effect of earthquakes on the occurrence of earthquake-induced landslides (Lin et al 2007;Marc et al 2015;Parker et al 2015). For instance, Marc et al (2015) demonstrated that landslide rates were significantly elevated within 0.7-4.5 years after four earthquakes with magnitude higher than 6 Richter.…”
Section: Are Follow-up Landslides Different?mentioning
confidence: 69%
“…Our results are most applicable to hillslope deposits of similar rheology and stress history to those tested here, indicative of shallow (~10 to 20 m depth) failures in near-surface slope materials, within which prefailure strain, manifest as ground cracking, is frequently evident. Our findings may also be applicable at the broader "landscape scale", where seismically controlled dilation controls the frictional strength of heavily damaged rock masses [Marc et al, 2015;Scheingross et al, 2013]. We have demonstrated that lower magnitude ground-shaking events can in some cases cause progressive densification of sediment, increasing frictional strength and reducing susceptibility to landsliding during subsequent seismicity and also in response to precipitation events.…”
Section: Discussionmentioning
confidence: 85%
“…As such, our understanding of both coseismic and interseismic landsliding rates and patterns is primarily empirical which potentially limits the transferability of patterns and transient rates of landsliding identified. Marc et al [2015] reported an exponential reduction in elevated landslide activity and a return to preseismic landslide rates over subdecadal timescales. The four case studies considered by Marc et al [2015] share broadly similar seismogenic settings, and all experienced an earthquake sequence characterized by a mainshock and a series of aftershocks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations